English Ability, Cultural Intelligence (CQ), Personality Traits and Service Quality—The Structural Relationship - Chu, Cindy; Hsu, Liwei (Journal of Ecohumanism, 2024)
In the tourism sector, the performing arts tourism market is rising. In Taiwan, more performing arts venues are being built, not only for performances but also to draw tourists. This study used the well-known tourist destination National Kaohsiung Center for the Arts (also known as "Weiwuying") as the research site. Weiwuying is an international venue, thus the professionalism and level of service provided by the staff merit discussion. This study investigated the personality characteristics, cultural intelligence, and English proficiency of the Weiwuying front-line workers. This study also examines visitor satisfaction and service quality. An online questionnaire served as the data collection tool for the study, which used the quantitative technique as its research strategy. Information was gathered from clients who possess visited Weiwuying. For the analysis, a sample size of 376 was used. In this study, the measurement and structural model were examined using Smart PLS 4.0. The study found that personality attributes and English proficiency have an impact on service quality. Customer happiness is influenced by service quality. However, the impact of cultural intelligence on service quality is minimal. The study also made recommendations for additional research and examined its theoretical and practical implications.